“La No Planificación De La Tarea Docente, Influye En El Proceso De Aprendizaje Significativo, En Los Estudiantes De La Unidad Educativa 24 De Mayo, Del Cantón Quevedo, Provincia De Los Ríos”. - Zúñiga Medina, Zúñiga Medina (2014)
End the current moments, the planning of the teaching task is of importance for the development of the class plan, promotes an active role in the student, built their own knowledge, and this teamwork, to develop the capacity of collaboration with the group, by exchanging ideas and experiences, allowing students to engage in the process of reflection on the learned, how learned and the use of the results that manage to be meaningful, lasting and authentic. Apply observation, it allowed different pedagogical activities that we carry out to managers, teachers and professors to attend and had approach to the problem which I researched; field study, helped me to manipulate the external variable not ascertained, in order to describe of how or why causes is there not planning the teaching task?; with the survey, this technique helped me to listen to the information which was intended to investigate; I based me, exclusively on a questionnaire which had full relationship with the approach of the hypotheses, enabling ask a series of questions to measure one or more variables. I also used the synthetic analytical method, conducted the analysis of the information and formulate conclusions and recommendations. Teachers in the educational unit "may 24" pledged to carry out the planning of the teaching task for better learning in students and are significant, enduring and authentic.